(untitled) (Actualité en allergologie et en immunologie au Canada, 2023)
It is imperative for allergists and immunologists to accurately confirm the diagnosis of HAE and coordinate individualized, patient-centred treatment. The 2019 International/Canadian Hereditary Angioedema Guideline, provides an evidence-based approach to managing HAE patients. The objective of this article is to further assist healthcare providers in caring for patients with a confirmed diagnosis of HAE by outlining an approach to patient counselling and reviewing the principles of therapy. We propose 5 essential items to consider in the management of all HAE patients: 1) Patient education; 2) On-demand therapy; 3) Short-term prophylaxis (STP); 4) Long-term prophylaxis (LTP); and 5) Genetic testing. We will also discuss special considerations for pregnant patients.